The organizational culture influence as a mediator between training development and employee performance in Iraqi Academic sector: University of Middle Technical - Ali, Ali Bashar Jamal; Ismail, Fadillah Binti; Sharif, Zainon Mat; Hamawandy, Nawzad Majeed; Abubakr, Zaito Awla; Qader, Khowanas Saeed; Othman, Bestoon (The journal of contemporary issues in business and government, 2021)
Employee performance is a critical issue for organizations especially in academic sector. It undermines the efficiency and productivity of the organization. There is a need of looking at factors that affect this behavior of the workforce. Therefore, this study focuses on the relationship of training development variables which are Perceived availability of training, Motivation to learn from training and Individual characteristic with organizational culture and employee performance in academic settings. This paper also determines whether organizational culture mediates the relationship between training development and employee performance. To have empirical evidence about these relationships, data will be collected from academic staff employed at public sector universities of Iraq using self- administered questionnaire. The collected will be analyzed using both descriptive and inferential statistics. Confirmatory factor analysis using Social Science Statistics Package (SPSS) version 23.0 to measure the relationship between variables and to test the hypotheses related to this study. This study contributes to body of knowledge by investigating the relationship of training development with workplace attitudes incorporating constructs of training development, organizational culture effect and employee performance using one comprehensive research framework. This paper will give an enhancement to the policy makers in higher education sector about the availability of training development opportunities which affect the performance of academic staff and in turn affect the effectiveness of universities as well.